Omalizumab Treated Urticaria Patients Display T Cell and Thrombocyte‐Associated Gene Regulation - Anna Smola; Heike C. Hawerkamp; Péter Oláh; Andreas Kislat; Nicole Duschner; Bernhard Homey; Stephan Meller (Immunity, Inflammation and Disease)
ABSTRACT Background Chronic spontaneous urticaria (CSU) is a debilitating inflammatory skin disease with a prevalence of approximately 1% of the population. It is characterized by recurrent itchy wheals and/or angioedema for more than 6 weeks without known triggers leading to a high quality of life impairment. The pathogenesis of CSU remains not fully understood. Objective This study aimed to explore the pathomechanism of CSU beyond mast cells and IgE‐dependent histamine release and to identify possible biomarkers for the disease and its treatment. Methods We investigated a patient cohort in the first month of omalizumab treatment regarding the IgE levels and changes in gene and miRNA expression in peripheral blood. The cohort was divided into responders and nonresponders (depending on the score of the urticaria control test) and compared to a group of healthy controls. Results Our messenger RNA and microRNA microarray analyses revealed the greatest changes in expression levels on Day 2 after the first omalizumab dose. Conclusion We identified several genes and miRNAs of interest, most of which have not been described to be linked to CSU so far, underlining, for example, to T cell involvement or even suggesting platelet involvement.